Building nations, dividing peoples: Israel, Syria and the struggle for the Druze - Stoker, Daniel W. (AUC Knowledge Fountain, 2012)
This thesis examines how the development of nationalism and foundation of nation-states in the Levant have contributed to the development of new national identities among the Druze communities in the Golan Heights and Israel and how it has impacted each community. This study builds on the ideas of Benedict Anderson and Eric Hobsbawm regarding nationalism and the development of the nation as both invented and imagined. This thesis then analyzes the policies of Israel and Syria regarding the Druze communities in the Golan Heights and the question of Druze feelings toward these policies. It also examines how Druze history has been framed in the context of the nation-state. Additionally this work examines how Israel and Syria's policies toward the Druze have created an economic reliance on the state while shaping national identity in the process. It also explores how Syria has facilitated agricultural development by assisting the Druze in the Golan Heights in the apple trade while weighing Israel's neglect of this community. Finally, I discuss the schism that exists between Israeli-Druze who support Israel and those who support Syria and whether or not national identities can be unimagined.